Using Gamification-based Program to Increase Student Creativity Skills in Sustainable Development Topics - Zuliande Zidan; Saefudin Saefudin; Kusnadi Kusnadi; Asyah Dwi Hastika (Jurnal Penelitian Pendidikan IPA, 2024)
Creativity skills are one of the essential skills to face the VUCA World. Improving creativity skills is hampered by the large number of students and learning conditions that are less demanding of the creative process in the class. This research aims to measure the effectiveness of the Botanical Eco-gamification program to improve creativity skills. The ADDIE research approach was used to redesign the Botanical Eco-gamification program so that it can improve creativity skills. This research produced test instruments, e-LAD and questionnaires to measure creativity skills in the program. The instrument developed has been proven valid and reliable for measuring originality, divergent thinking, convergent thinking and mental flexibility skills. The results of program implementation show that students' creativity skills have increased from before treatment in the sufficient category (54.2) to the good category (71.16) with the N-Gain achievement being categorized as medium (0.37). The majority of students (55.71%) reached mastery level after being given treatment. Almost all students (76.29%) stated that the program was good for improving creativity skills. Further research is needed to examine other 4cs competencies, ESD competencies, mastery learning and student's engagement in the Botanical Eco-gamification program